Spherical H13-TiB2 composite powder as well as preparation method and application thereof
By designing spherical H13-TiB2 composite powder, using Fe-Ti-B reaction system and multi-directional forging technologies, the uniform distribution and refinement of TiB2 particles is achieved, solving the problem of weak interface bonding between ceramic particles and matrix and enhancing phase agglomeration, and improving the comprehensive performance of the composite material.
Patent Information
- Application Number
- CN202411955468.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when preparing metal-based composite materials, the interface bond between the ceramic particles and the substrate is weak, which enhances phase agglomeration, resulting in difficulty in synergistically improving the strength-plastic toughness, wear resistance and high-temperature performance of the composite material.
Using the preparation method of spherical H13-TiB2 composite powder, the design of the Fe-Ti-B reaction system is used to generate the TiB2 enhanced phase in situ, and combined with multi-directional forging and plasma rotary electrode atomization technology, the uniform distribution and refinement of TiB2 particles is achieved.
The uniform distribution and refinement of TiB2 particles in the H13 steel matrix is achieved, which enhances the strength, plastic toughness, wear resistance and high temperature performance of the composite material, and solves the problems of incomplete enhancement phase reaction and agglomeration in traditional methods.
Smart Images

Figure CN119703044A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal-based composite powder preparation, and specifically relates to a spherical H13-TiB2 composite powder and a preparation method and application thereof. Background Art
[0002] As a medium-carbon alloy steel of the Cr-Mo-V series, H13 steel has excellent strength and toughness, good hardenability, high softening resistance and excellent high-temperature friction resistance. It is widely used in die-casting dies, forging dies and hot extrusion dies, and has become one of the representative hot working die steels. Modern industry has put forward higher service requirements for the performance of tool steel, such as hardness, room / high temperature toughness and wear resistance. However, the use of traditional methods such as steel matrix microalloying, ultrapurification and heat treatment processes to improve the performance of steel has almost reached a bottleneck. In recent years, the introduction of ceramic particles and the compounding of the steel matrix to improve the elastic modulus, hardness and wear resistance of the steel matrix has become a research and development strategy to effectively improve the comprehensive performance of the steel matrix.
[0003] At present, the common ceramic reinforcement phases used for steel matrix mainly include oxides (Al2O3), nitrides (TiN), carbides (TiB2, SiC, WC, etc.) and borides (TiB, TiB2, ZrB2). Among them, borides have the characteristics of high modulus and low density, and have attracted extensive attention from researchers. TiB2 has high elastic modulus, high thermal stability, low density (4.5 g / cm 3 ), low thermal expansion coefficient (5.5×10 -6 / K). Studies have shown that TiB2 can be precipitated in situ through the Fe-Ti-B pseudo-binary eutectic reaction, that is, the in-situ generation of TiB2 ceramic phase is achieved through the smelting process, and a good interface bonding is formed between the TiB2 and the iron matrix. Compared with the external addition method, in-situ self-generated TiB2 reinforced steel and iron-based composites usually have better mechanical properties.
[0004] In recent years, the in-situ self-generation method has become one of the key technologies for preparing high-performance metal-based composites. Its preparation idea is to generate a ceramic reinforcement phase with high hardness, high elastic modulus and high thermal stability in the metal matrix through chemical reaction, so as to achieve the purpose of strengthening the metal matrix. For example, traditional medium-high carbon steel can be regarded as in-situ self-generated nanocarbide reinforced steel. In-situ self-generated ceramic particles have good thermal stability, no need to consider the wettability and interface reaction between the self-generated particles and the matrix, and the particles are evenly distributed in the matrix and have a small size (micro-nano level). For H13 steel-based composites, the traditional strengthening method is to introduce ceramic particles through external addition (mechanical mixing, mechanical alloying). There are many problems with the above strengthening methods, such as (1) the interface between ceramic particles and the matrix is weak and the bonding strength is low; (2) the ceramic particles have poor dispersion and are easy to agglomerate; (3) the ceramic particle size control window is narrow, and the growth and coarsening of the reinforcement phase has a serious effect on the matrix. This makes the excellent intrinsic properties of ceramic particles have limited strengthening effect on composites. At present, the main preparation technologies of particle-reinforced metal matrix composites are: fusion-casting, powder metallurgy (PM), additive manufacturing (AM), etc. Powder metallurgy uses metal powder as raw material, and achieves rapid preparation of materials through pre-pressing and curing sintering. It has the characteristics of high flexibility in reaction design, high raw material utilization rate, and good microstructure uniformity. Additive manufacturing technology is based on the "discrete-accumulation" principle, combining computer-aided three-dimensional modeling, slicing and rapid prototyping technology, and using high-energy beams (lasers, electron beams) to quickly melt and solidify pre-alloyed powders and deposit them layer by layer to form near-net-shape high-performance and dense metal parts. Compared with traditional preparation technologies, additive manufacturing technology has significant advantages in forming high-precision and complex parts, and therefore shows broad application prospects in high-end equipment manufacturing fields such as aerospace, biomedicine and rail transportation.
[0005] As a key raw material for advanced manufacturing, metal powder has become one of the research hotspots in the field of powder metallurgy and additive manufacturing. High-performance spherical metal powders prepared by atomization powder making technology (VIGA, EIGA and PREP) are widely used in the field of advanced manufacturing because of their advantages such as high sphericity, good fluidity, and low impurity and oxygen content. However, in the study of the preparation of metal-based composites by traditional powder metallurgy and additive manufacturing, the premixed powders prepared by ball milling have problems such as powder contamination, uneven mixing, and poor fluidity caused by the destruction of sphericity, which ultimately lead to inclusions, internal defects, incomplete reaction of the reinforcement phase, and weak interface bonding between the reinforcement phase and the matrix in the prepared composite materials. This limits the performance improvement of ceramic particles on the metal matrix. Summary of the invention
[0006] The purpose of the present invention is to provide a spherical H13-TiB2 composite powder and a preparation method and application thereof, so as to solve the technical problem that it is difficult to synergistically improve the strength-plasticity, wear resistance and high temperature performance of the composite material due to the existing preparation method, such as agglomeration of the reinforcing phase in the prepared composite material and weak interface bonding with the matrix.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a spherical H13-TiB2 composite powder. Calculated by mass percentage, raw materials of the spherical H13-TiB2 composite powder include 1.55-6.22 wt.% B powder, 3.45-13.78 wt.% titanium material and 95%-80wt.% H13 steel material.
[0008] Furthermore, in the spherical H13-TiB2 composite powder, the content of in-situ self-generated TiB2 is 5-20 wt.%; The titanium material is titanium sponge particles or titanium powder; the average particle size of the B powder is about 5 μm; the average particle size of the titanium material is about 10 mm or 45 μm.
[0009] The present invention also discloses a method for preparing the spherical H13-TiB2 composite powder, comprising the following steps: Weigh B powder, titanium material and H13 steel material according to the above mass percentage for later use; H13 steel material, B powder and titanium material are placed in a melting furnace in order from bottom to top, and then vacuumed for induction heating melting to obtain an H13-TiB2 composite material ingot; Then, the H13-TiB2 composite material ingot is subjected to die forging treatment to obtain a forged H13-TiB2 composite material; The forged H13-TiB2 composite material is machined to obtain a consumable electrode rod; the consumable electrode rod is melted and atomized to obtain a spherical H13-TiB2 composite powder.
[0010] Furthermore, an iron foil is placed between the H13 steel material and the B powder; the purity of the iron foil is 99.9%; The vacuum degree of the induction heating melting is 4.5~5×10 -3 Pa; the method used for the induction heating melting is cold crucible suspension melting; the temperature of the induction heating melting is 1600~1800 ℃, and the time is 15~20 min; The induction heating melting is repeated 1 to 2 times.
[0011] Furthermore, before the H13-TiB2 composite material ingot is subjected to die forging treatment, the H13-TiB2 composite material ingot is subjected to high temperature homogenization treatment; the process parameters of the high temperature homogenization treatment are: Raise the temperature to 900 ℃ at 10-20 ℃ / min, keep it at that temperature for 2 h, then raise the temperature to 1150 ℃ at 10-15 ℃ / min, keep it at that temperature for 1 h.
[0012] Furthermore, the process parameters of the die forging process are: preheating the forging hammer to 500-550°C, then forging the H13-TiB2 composite material in the axial and radial directions with a deformation of 50%, and the final forging temperature is not less than 1000°C; the forging process is re-melted 2-3 times; The temperature of the remelting treatment is 1150-1180°C, and the holding time is 20-25 min.
[0013] Furthermore, the smelting atomization adopts plasma rotating electrode atomization; the parameters of the plasma rotating electrode atomization are: the maximum working speed of the electrode rod is 30000 rpm, the powder particle size collection interval is set to 45~150 μm, and the atomization process is carried out under argon or helium protection.
[0014] Furthermore, the H13 steel material is H13 steel ingot.
[0015] The invention also discloses the application of the spherical H13-TiB2 composite powder in 3D printing.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a spherical H13-TiB2 composite powder. By means of component design, the mass percentage contents of B powder, titanium material and steel material are regulated to realize the progress of the Fe-Ti-B reaction system and inhibit the generation of Fe-B intermediate phase, so that TiB2 is evenly distributed in an H13 steel matrix in a nanometer or submicron size. The invention solves many problems in powder metallurgy and additive manufacturing, such as uneven mixing of reinforcement phase and matrix raw material, easy introduction of impurities, destruction of sphericity, incomplete reaction of reinforcement phase particles in the prepared composite material and easy agglomeration, etc., which are caused by using traditional premixed powder as raw material.
[0017] The present invention also discloses a method for preparing the spherical H13-TiB2 composite powder, which transforms the in-situ reaction-diffusion-growth mechanism of the reinforcing phase particles in the traditional in-situ self-generated TiB2 particle-reinforced steel-based composite material into a supersaturated solid solution-nucleation-precipitation-growth mechanism of the reinforcing phase forming element (Ti-B). First, the H13-Ti-B component is designed and demonstrated based on the in-situ reaction of the Fe-Ti-B system; then, the high temperature conditions of the vacuum melting process are used to realize the in-situ precipitation reaction between B and Ti elements, so that TiB2 particles are precipitated in-situ in the H13 steel liquid; then, the molten-cast H13-TiB2 composite material is refined by a multi-directional forging process in order to crush the coarse primary TiB2 particles; finally, atomization powder making is used. The technical remelting, centrifugal atomization and rapid cooling solidification process are used to refine and homogenize the TiB2 particle size and distribution, and finally a spherical H13-TiB2 composite powder containing nano or submicron TiB2 reinforcement phase is obtained. The TiB2 particles prepared by the Fe-Ti-B in-situ reaction have good wettability with the steel (iron) matrix, which can overcome the shortcomings of poor wettability and low bonding strength between the added ceramic particles and the matrix material; secondly, with the help of plasma arc melting, centrifugation and rapid cooling solidification in the plasma rotating electrode atomization process, the coarse primary TiB2 particles in the molten-cast H13-TiB2 structure can be further refined, and the in-situ precipitation reaction of TiB2 can be promoted, so as to achieve uniform distribution of nano and submicron TiB2 in the H13 steel-based composite powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a metallographic microstructure diagram of the forged H13-TiB2 composite material prepared by the present invention; Figure 2 This is a surface morphology diagram of the spherical H13-TiB2 composite powder of the present invention; Among them: a-SEM of powder at 200X magnification; b-SEM of single powder at 500X magnification; Figure 3 This is a cross-sectional morphology diagram of the spherical H13-TiB2 composite powder of the present invention; Among them: a-SEM morphology of powder cross section; b-high magnification SEM morphology of TiB2 distribution in powder cross section; Figure 4 This is the X-ray diffraction spectrum of the spherical H13-TiB2 composite powder of the present invention. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0020] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0021] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0022] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0023] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0024] The present invention provides a spherical H13-TiB2 composite powder. The raw materials are designed according to the following mass percentages: 1.55-6.22 wt.% of B powder, 3.45-13.78 wt.% of sponge titanium particles (or titanium powder), 95%-80 wt.% of H13 steel material, and the sum of the mass percentages of the above components is 100%.
[0025] Based on the original Ti and B content design, the in-situ self-generated TiB2 content in the final composite powder is 5~20wt.%; among them, the average particle size of B powder is about 5 μm, and the purity is 99%; the average particle size of sponge titanium particles (or titanium powder) is about 10mm or 45 μm, and the purity is about 99.8%; the H13 steel material is H13 steel ingot, which is irregular in shape. The specific composition of each raw material is shown in the table below.
[0026] Table 1 Chemical composition of H13 steel materials (wt.%)
[0027] Table 2 Chemical composition of titanium sponge (wt.%)
[0028] Table 3 Chemical composition of B powder (wt.%)
[0029] The present invention also discloses a method for preparing the spherical H13-TiB2 composite powder, which is specifically implemented according to the following steps: Step 1: Weigh the raw materials According to the designed content of in-situ self-generated TiB2 of 5-20 wt.%, 1.56-6.22 wt.% of B powder, 4.99-15.33 wt.% of sponge titanium particles (or titanium powder) (including 1.55 wt.% excess Ti design), and 95%-80 wt.% of H13 steel ingot are weighed respectively according to the mass percentage. The sum of the mass percentages of the above raw materials is 100%; Step 2: Smelting Preparation The B powder weighed in step 1 was pre-pressed by a hydraulic press, with a size of 30 mm × 5 mm. Then, H13 steel material, B powder and titanium material were placed in a 20 kg melting furnace from bottom to top. In order to slow down the reaction between boron and iron elements (H13 steel), high-purity iron foil (purity 99.9%, size 0.02*150*150 mm) was placed between the H13 steel material and the B powder. The Fe element increment brought by the introduction of high-purity iron foil was less than 0.06%. In addition, according to the Fe-Ti-B reaction system, the raw material composition was designed, and the overall excess of Ti element was 1.55 wt.% to inhibit the formation of Fe-B intermediate phase. After the above raw materials were loaded and prepared correctly, the melting furnace was vacuumed. Step 3: Cold Crucible Magnetic Levitation Melting The above raw materials are induction heated and melted by cold crucible suspension melting technology. B powder contacts with sponge titanium particles (or titanium powder) at high temperature to generate TiB2 reinforcement phase in situ. In order to promote the in-situ reaction of Ti-B during the melting process, the induction heating melting is repeated 1 to 2 times to ensure sufficient reaction between the raw materials and homogenization of the in-situ self-formed TiB2 particles. After the melting is completed, the raw materials are cooled to room temperature with the furnace to obtain H13-TiB2 composite material ingots with a size of 200 mm × 150 mm. Step 4: Multi-directional forging process The H13-TiB2 composite ingot was forged by a 500 T forging press. Before forging, the H13-TiB2 ingot was subjected to high-temperature homogenization treatment using a box-type resistance furnace. The specific parameters were as follows: heating to 900°C at 10-20°C / min, keeping warm for 2 h, and then heating to 1150°C at 10-15°C / min, keeping warm for 1 h. Subsequently, the preheated ingot was forged, and the forging deformation along the axial and radial directions was 50%. The final forging temperature was not less than 1000°C. In order to ensure the radial drawing allowance, the forging process was returned to the furnace for 2-3 times. The specific parameters were 1150-1180°C and kept warm for 20-25 min. Finally, the H13-TiB2 forgings that met the deformation requirements were die forged to obtain a forged H13-TiB2 composite material with coaxial height and no surface cracks. Step 5: Preparation of consumable electrode rods The forged H13-TiB2 composite material was machined to obtain a consumable electrode bar with a size of 52 mm × 260 mm that meets the requirements of plasma rotating electrode atomization. Step 6: Preparation of spherical H13-TiB2 pre-alloyed composite powder The H13-TiB2 consumable electrode obtained in step 5 is melted and atomized by plasma rotating electrode atomization technology to finally obtain spherical H13-TiB2 pre-alloyed composite powder.
[0030] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0031] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0032] Example 1 A method for preparing spherical H13-TiB2 composite powder comprises the following steps: According to the mass percentage, 1.56wt.% B powder, 4.99wt.% titanium powder (containing an excess of 1.55wt.% Ti to avoid the formation of Fe-B brittle phase) and 95wt.% H13H13 steel ingot were weighed as raw materials for use; H13 steel material, B powder and titanium material are placed in the melting furnace in order from bottom to top, and then vacuumed to 4.5~5×10 -3 Pa, repeated induction heating melting twice by cold crucible suspension melting method, to obtain H13-TiB2 composite material ingot; wherein, iron foil was placed between H13 steel material and B powder, the purity of iron foil was 99.9%, and the size was 0.02*150*150 mm; the parameters of induction heating melting were 12KHz high frequency magnetic field heating conditions, the raw material was heated to 1650 ℃, and smelted for 15 min to ensure uniform melt reaction; The H13-TiB2 composite material ingot was subjected to high-temperature homogenization treatment; the process parameters of the high-temperature homogenization treatment were: heating to 900 °C at 15 °C / min, keeping warm for 2 h, and then heating to 1150 °C at 10 °C / min, keeping warm for 1 h; then, a 500 T forging press was used for die forging, the forging hammer was preheated to 500 °C, and then the preheated ingot was forged, the axial forging deformation was 50%, and the final forging temperature was not less than 1000 °C. In order to ensure the radial drawing allowance, the forging process was returned to the furnace for 3 times, and the specific parameters were 1150 °C and kept warm for 20 min, and a forged H13-TiB2 composite material with coaxial height and no surface cracks was obtained; The forged H13-TiB2 composite material was machined to obtain a consumable electrode bar with a size of 52 mm × 260 mm that meets the requirements of plasma rotating electrode atomization. The consumable electrode rod was melted and atomized by plasma rotating electrode atomization technology, and spherical H13-TiB2 pre-alloyed composite powder was finally obtained; the melting and atomization parameters were as follows: the maximum working speed of the electrode rod was 30000 rpm, the powder particle size collection range was set to 45~150 μm, and the atomization process was carried out under argon or helium protection.
[0033] Example 2 A method for preparing spherical H13-TiB2 composite powder comprises the following steps: According to the mass percentage, 3.11wt.% B powder, 8.44wt.% (including 1.55wt.% excess Ti to avoid the formation of Fe-B brittle phase) titanium powder and 90wt.% H13 steel ingot were weighed as raw materials for use; H13 steel material, B powder and titanium material are placed in the melting furnace in order from bottom to top, and then vacuumed to 4.5~5×10 -3Pa, repeated induction heating melting 2-3 times by cold crucible suspension melting method, to obtain H13-TiB2 composite material ingot; wherein, iron foil was placed between H13 steel material and B powder, the purity of iron foil was 99.9%, and the size was 0.02*150*150 mm; the parameters of induction heating melting were: under 12KHz high frequency magnetic field heating conditions, the raw material was heated to 1650 ℃, and melted for 15 min to ensure uniform melt reaction; The H13-TiB2 composite material ingot is subjected to high-temperature homogenization treatment; the process parameters of the high-temperature homogenization treatment are: heating to 900 ℃ at 15 ℃ / min, keeping warm for 2 h, and then heating to 1150 ℃ at 10 ℃ / min, keeping warm for 1 h; then a 500 T forging press is used for die forging, the forging hammer is preheated to 550 ℃, and then the preheated ingot is forged, the forging deformation along the axial and radial directions is 50%, and the final forging temperature shall not be lower than 1000 ℃. In order to ensure the radial drawing allowance, the forging process is returned to the furnace for 3 times, and the specific parameters are 1150 ℃ and keeping warm for 20 min, so as to obtain a forged H13-TiB2 composite material with coaxial height and no surface cracks; the obtained forged H13-TiB2 composite material is machined to obtain a consumable electrode bar with a size of 52 mm×260 mm that meets the requirements of plasma rotating electrode atomization; The consumable electrode rod was melted and atomized by plasma rotating electrode atomization technology, and spherical H13-TiB2 pre-alloyed composite powder was finally obtained; the melting and atomization parameters were as follows: the electrode rod working speed was 22000-26000 rpm, the powder particle size collection range was set to 45-150 μm, and the atomization process was carried out under argon or helium protection.
[0034] Example 3 A method for preparing spherical H13-TiB2 composite powder comprises the following steps: According to the mass percentage, 4.67wt.% B powder, 11.88wt.% (including 1.55wt.% excess Ti to avoid the formation of Fe-B brittle phase) titanium powder and 85wt.% H13 steel ingot are weighed as raw materials for use; H13 steel material, B powder and titanium material are placed in the melting furnace in order from bottom to top, and then vacuumed to 4.5~5×10 -3Pa, repeated induction heating melting 2-3 times by cold crucible suspension melting method, to obtain H13-TiB2 composite material ingot; wherein, iron foil was placed between H13 steel material and B powder, the purity of iron foil was 99.9%, and the size was 0.02*150*150 mm; the parameters of induction heating melting were: under 12KHz high frequency magnetic field heating conditions, the raw material was heated to 1750 ℃, and melted for 15 min to ensure uniform melt reaction; The H13-TiB2 composite material ingot is subjected to high-temperature homogenization treatment; the process parameters of the high-temperature homogenization treatment are: heating to 900 ℃ at 15 ℃ / min, keeping warm for 2 h, and then heating to 1150 ℃ at 10 ℃ / min, keeping warm for 1 h; then a 500 T forging press is used for die forging, the forging hammer is preheated to 550 ℃, and then the preheated ingot is forged, the forging deformation along the axial and radial directions is 50%, and the final forging temperature shall not be lower than 1000 ℃. In order to ensure the radial drawing allowance, the forging process is returned to the furnace for 3 times, and the specific parameters are 1150 ℃ and keeping warm for 20 min, so as to obtain a forged H13-TiB2 composite material with coaxial height and no surface cracks; the obtained forged H13-TiB2 composite material is machined to obtain a consumable electrode bar with a size of 52 mm×260 mm that meets the requirements of plasma rotating electrode atomization; The consumable electrode rod was melted and atomized by plasma rotating electrode atomization technology, and spherical H13-TiB2 pre-alloyed composite powder was finally obtained; the melting and atomization parameters were as follows: the electrode rod working speed was 22000-26000 rpm, the powder particle size collection range was set to 45-150 μm, and the atomization process was carried out under argon or helium protection.
[0035] Example 4 A method for preparing spherical H13-TiB2 composite powder comprises the following steps: According to the mass percentage, 6.22wt.% B powder, 15.33wt.% (including 1.55wt.% excess Ti to avoid the formation of Fe-B brittle phase) titanium powder and 80wt.% H13 steel ingot are weighed as raw materials for use; H13 steel material, B powder and titanium material are placed in the melting furnace in order from bottom to top, and then vacuumed to 4.5~5×10 -3Pa, repeated induction heating melting 2-3 times by cold crucible suspension melting method, to obtain H13-TiB2 composite material ingot; wherein, iron foil was placed between H13 steel material and B powder, the purity of iron foil was 99.9%, and the size was 0.02*150*150 mm; the parameters of induction heating melting were: under 12KHz high frequency magnetic field heating conditions, the raw material was heated to 1750 ℃, and smelted for 20 min to ensure uniform melt reaction; The H13-TiB2 composite material ingot was subjected to high-temperature homogenization treatment; the process parameters of the high-temperature homogenization treatment were: heating to 900 °C at 15 °C / min, keeping warm for 2 h, and then heating to 1150 °C at 10 °C / min, keeping warm for 1 h; then a 500 T forging press was used for die forging, the forging hammer was preheated to 550 °C, and then the preheated ingot was forged, the axial and radial forging deformation was 50%, and the final forging temperature was not less than 1000 °C. In order to ensure the radial drawing allowance, the forging process was returned to the furnace for 3 times, and the specific parameters were 1150 °C and kept warm for 20 min, and a forged H13-TiB2 composite material with coaxial height and no surface cracks was obtained; The forged H13-TiB2 composite material was machined to obtain a consumable electrode bar with a size of 52 mm × 260 mm that meets the requirements of plasma rotating electrode atomization. The consumable electrode rod was melted and atomized by plasma rotating electrode atomization technology, and spherical H13-TiB2 pre-alloyed composite powder was finally obtained; the melting and atomization parameters were as follows: the electrode rod working speed was 22000-26000 rpm, the powder particle size collection range was set to 45-150 μm, and the atomization process was carried out under argon or helium protection.
[0036] Figure 1 This is the forged metallographic microstructure of the H13-TiB2 composite material prepared by smelting casting + forging in the present invention; it can be seen that the in-situ self-generated TiB2 particles have a nearly spherical and eutectic dendritic morphology, with an average size of about 10 μm, and the TiB2 particles have obvious orientation distribution characteristics along the forging direction.
[0037] Figure 2 The surface morphology of the H13-TiB2 pre-alloyed composite powder prepared by the present invention; Figure 2 (a) It can be seen that the composite powder prepared by plasma rotating electrode atomization method has a smooth surface, high sphericity, and no satellite powder; Figure 2 (b) It can be seen that larger micron-sized TiB2 particles are distributed on the surface of a single powder.
[0038] Figure 3The cross-sectional morphology of the H13-TiB2 pre-alloyed composite powder prepared by the present invention; Figure 3 (a) It can be seen that the cross section of the composite powder has a network-like structure; Figure 3 (b) shows that the composite powder has a typical cellular structure caused by non-equilibrium solidification, and micro-nano sized TiB2 particles are distributed at the boundaries of the cellular structure.
[0039] Figure 4 This is the X-ray diffraction spectrum of the H13-TiB2 pre-alloyed composite powder prepared by the present invention; the results show that the phase composition of the composite powder is mainly ferrite matrix, in-situ self-generated TiB2 and a small amount of austenite, without other impurity phases, indicating that the powder purity is relatively high.
[0040] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A spherical H13-TiB2 composite powder, characterized in that: In terms of mass percentage, the raw materials of the spherical H13-TiB2 composite powder include 1.55-6.22 wt.% B powder, 3.45-13.78 wt.% titanium material and 80%-95 wt.% H13 steel material.
2. A spherical H13-TiB2 composite powder according to claim 1, characterized in that: In the spherical H13-TiB2 composite powder, the content of in-situ self-generated TiB2 is 5-20 wt.%; The titanium material is titanium sponge particles or titanium powder; the average particle size of the B powder is about 5 μm; the average particle size of the titanium material is about 10 mm or 45 μm.
3. The method for preparing a spherical H13-TiB2 composite powder according to claim 1 or 2, characterized in that: The following steps are involved: Weigh B powder, titanium material and H13 steel material according to the mass percentage of claim 1 for use; H13 steel material, B powder and titanium material are placed in a melting furnace in order from bottom to top, and then vacuumed for induction heating melting to obtain an H13-TiB2 composite material ingot; Then, the H13-TiB2 composite material ingot is subjected to die forging treatment to obtain a forged H13-TiB2 composite material; The forged H13-TiB2 composite material is machined to obtain a consumable electrode rod; the consumable electrode rod is melted and atomized to obtain a spherical H13-TiB2 composite powder.
4. The method for preparing a spherical H13-TiB2 composite powder according to claim 3, characterized in that: An iron foil is placed between the H13 steel material and the B powder; the purity of the iron foil is 99.9%; The vacuum degree of the induction heating melting is 4.5~5×10 -3 Pa; the method used for the induction heating melting is cold crucible suspension melting; the temperature of the induction heating melting is 1600~1800 ℃, and the time is 15~20 min; The induction heating melting is repeated 1 to 2 times.
5. The method for preparing a spherical H13-TiB2 composite powder according to claim 3, characterized in that: Before the H13-TiB2 composite material ingot is subjected to die forging treatment, the H13-TiB2 composite material ingot is subjected to high temperature homogenization treatment; the process parameters of the high temperature homogenization treatment are: Raise the temperature to 900 ℃ at 10-20 ℃ / min, keep it at that temperature for 2 h, then raise the temperature to 1150 ℃ at 10-15 ℃ / min, keep it at that temperature for 1 h.
6. The method for preparing a spherical H13-TiB2 composite powder according to claim 3, characterized in that: The process parameters of the die forging treatment are: preheating the forging hammer to 500-550°C, then forging the H13-TiB2 composite material in the axial and radial directions with a deformation of 50%, and the final forging temperature is not less than 1000°C; the forging process is re-melted 2-3 times.
7. The method for preparing a spherical H13-TiB2 composite powder according to claim 3, characterized in that: The temperature of the remelting treatment is 1150-1180°C, and the holding time is 20-25 min.
8. The method for preparing a spherical H13-TiB2 composite powder according to claim 3, characterized in that: The smelting atomization adopts plasma rotating electrode atomization; the parameters of the plasma rotating electrode atomization are: the maximum working speed of the electrode rod is 30000 rpm, the powder particle size collection range is set to 45~150 μm, and the atomization process is carried out under argon or helium protection.
9. The method for preparing a spherical H13-TiB2 composite powder according to claim 3, characterized in that: The H13 steel material is H13 steel ingot.
10. Use of the spherical H13-TiB2 composite powder according to claim 1 or 2 in 3D printing.